2020
DOI: 10.1186/s41702-020-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

Activity of catechins and their applications

Abstract: Background: Catechins, which are polyphenol compounds found in many plants and are an important component of tea leaves, are strong anti-oxidants. Research: Many studies seek to enhance the effects of catechins on the human body and boost their protective power against UV radiation. There are many examples of the positive anti-microbial, anti-viral, anti-inflammatory, anti-allergenic, and anti-cancer effects of catechins. Catechins increase the penetration and absorption of healthy functional foods and bio cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(137 citation statements)
references
References 78 publications
5
113
0
1
Order By: Relevance
“…These results were in line with other previous studies where it has been observed that increase in circulating free fatty acids enhances hepatic TGs production. High TGs content associated with formation of an atherogenic dyslipidaemia consisting of an elevation in high TG content, low HDL cholesterol and increased LDL or apo lipoprotein-B [ 19 , 30 ]. Epidemiological studies indicated that regular intake of more than two cups of green tea and its catechin have been shown to ameliorate oxidative stress, hyperlipidemia and lower the concentration of TC and LDL, which has also been demonstrated in the performed meta-analysis of randomized clinical trials [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results were in line with other previous studies where it has been observed that increase in circulating free fatty acids enhances hepatic TGs production. High TGs content associated with formation of an atherogenic dyslipidaemia consisting of an elevation in high TG content, low HDL cholesterol and increased LDL or apo lipoprotein-B [ 19 , 30 ]. Epidemiological studies indicated that regular intake of more than two cups of green tea and its catechin have been shown to ameliorate oxidative stress, hyperlipidemia and lower the concentration of TC and LDL, which has also been demonstrated in the performed meta-analysis of randomized clinical trials [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are the most potent antioxidant identified in significant amounts in fruit and vegetable. Catechin is one of the most important flavonoids, with a comparatively high antioxidant activity [ 19 ]. Catechins have the beneficial effect of preventing skin damage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobial and antiviral (showed inhibition against Herpes simplex virus type 1 (HSV-1) (Musarra-Pizzo et al, 2019) Anti-oxidant, antitumor, antibacterial, antifungal, antidiabetic, anti-inflammatory, antiproliferative and antitumor (Cosarcã et al, 2019) Antioxidant, UV protective, anti-allergenic, anti-inflammatory, anti-microbial, anti-viral and anti-cancer (Bae et al, 2020) Antiviral (showed inhibition against pandemic influenza A (H1N1) (You et al, 2018) Epicatechin Antiviral (showed inhibitory effect against Mayaro (MAYV) virus and other alphavirus viruses (Ferreira et al, 2018) Antinociceptive and anti-inflammatory (Dias et al, 2018) Antibacterial (Ezhil and Lakshmi, 2017) Antidiabetic (Ibrahim et al, 2018) Anti-infective (Song, 2017) Anti-oxidant, antimicrobial, anti-inflammatory, antitumor, antidiabetic, anticancer and cardioprotective (Prakash et al, 2019) Antioxidant and anticollagenase (showed a high inhibitory power against the collagenase enzyme, responsible for the degradation of matrix collagen and the photo-aging process. (Geeta et al, 2019) UV protection (Prasanth et al, 2020)…”
Section: Catechinmentioning
confidence: 99%